ANALISIS RASIO KEUANGAN BANK UMUM YANG TERDAFTAR DI BURSA EFEK INDONESIA - Botutihe, Syamsurizal; Lamuda, Ilyas; Hasanuddin, Hasanuddin; Abdullah, Julie (Program Studi Akuntansi, 2023)
This study aims to analyze the financial ratios of commercial banks listed on the Indonesia Stock Exchange. The analytical method used is financial ratios consisting of profitability ratios, liquidity ratios, company growth ratios, capital structure ratios and company value ratios. The results of the study show that the average profitability ratio of the commercial banks studied cannot be said to meet the standards. Furthermore, the average liquidity ratio of the bank under study does not meet the standard ratio. For the company's growth ratio, only Bank Mandiri in 2021 meets the standards. The results of the ratio of the capital structure of the banking companies of all the banks studied on average met banking standards and lastly for the ratio of company values of all the banks studied, on average they met the standard ratio.